Imaging of translocator protein upregulation is selective for pro‐inflammatory polarized astrocytes and microglia. Issue 2 (3rd September 2019) - Pannell, Maria; Economopoulos, Vasiliki; Wilson, Thomas C.; Kersemans, Veerle; Isenegger, Patrick G.; Larkin, James R.; Smart, Sean; Gilchrist, Stuart; Gouverneur, Véronique; Sibson, Nicola R.
Abstract: Translocator protein (TSPO) expression is increased in activated glia, and has been used as a marker of neuroinflammation in PET imaging. However, the extent to which TSPO upregulation reflects a pro‐ or anti‐inflammatory phenotype remains unclear. Our aim was to determine whether TSPO upregulation in astrocytes and microglia/macrophages is limited to a specific inflammatory phenotype. TSPO upregulation was assessed by flow cytometry in cultured astrocytes, microglia, and macrophages stimulated with lipopolysaccharide (LPS), tumor necrosis factor (TNF), or interleukin‐4 (Il‐4). Subsequently, mice were injected intracerebrally with either a TNF‐inducing adenovirus (AdTNF) or IL‐4. Glial expression of TSPO and pro‐/anti‐inflammatory markers was assessed by immunohistochemistry/fluorescence and flow cytometry. Finally, AdTNF or IL‐4 injected mice underwent PET imaging with injection of the TSPO radioligand 18 F‐DPA‐713, followed by ex vivo autoradiography. TSPO expression was significantly increased in pro‐inflammatory microglia/macrophages and astrocytes both in vitro, and in vivo after AdTNF injection ( p  < .001 vs. control hemisphere), determined both histologically and by FACS. Both PET imaging and autoradiography revealed a significant ( p  < .001) increase in 18 F‐DPA‐713 binding in the ipsilateral hemisphere of AdTNF‐injected mice. In contrast, no increase in either TSPO expression assessed histologically and by FACS, or ligand binding by PET/autoradiography was observed after IL‐4 injection. Taken together, these results suggest that TSPO imaging specifically reveals the pro‐inflammatory population of activated glial cells in the brain in response to inflammatory stimuli. Since the inflammatory phenotype of glial cells is critical to their role in neurological disease, these findings may enhance the utility and application of TSPO imaging. Main points: TSPO expression is strongly associated with pro‐ but not anti‐inflammatory microglia, macrophages and astrocytes, in vitro and in vivo. PET imaging with TSPO ligand 18F‐DPA‐713 reveals the pro‐inflammatory population of glial cells.